Hanan Attaki's Humanist Preaching:: Efforts to Ground Islamic Communication in the Midst of Social Life in the Digital Era - Akbar Aldi Kautsar; Abdullah; Afwan Syahril Manurung (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The purpose of this study is to describe and analyze the humanist preaching strategy applied by Hannan Attaki in conveying Islamic messages in the digital era and to what extent the effectiveness of the Islamic communication approach used by Hannan Attaki in grounding Islamic values ​​in the midst of the social life of the digital society. The research method used is Qualitative Content Analysis, Data Collection and Sources using Instametrica and documentation. The results of the study show that the humanist da'wah strategy implemented by Hannan Attaki through digital media has proven effective in conveying Islamic values ​​contextually, empathetically, and inclusively, especially to the young urban generation in the digital era. This approach prioritizes reflective and down-to-earth communication through the use of a relaxed language style, storytelling techniques, and visualizations that are interesting and relevant to the audience's daily life. Hannan's lectures not only build a cognitive understanding of Islam, but also touch the emotional and psychosocial side of the audience, thus encouraging spiritual transformation and behavioral change. By combining the principles of da'wah bil hikmah and a communicative psychosocial approach, Hannan Attaki's da'wah becomes a model of contemporary Islamic communication that not only conveys religious messages, but also creates a friendly, adaptive, and empowering religious space.